(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
FRUITYLICIOUS is a business that was born out of the creative collaboration of four individuals who shared a passion for healthy and delicious food. They aimed to replace conventional foods like peach mango pie with more exciting and innovative options, resulting in unique and flavorful dishes that were both nutritious and tasty. Fruitylicious projects a high return on investment (ROI) of 485.09%. This means that for every peso invested in the business, an expected return of approximately 4.85 pesos is anticipated. While this indicates the potential profitability of the investment, it is important to consider other factors, such as risk and market conditions. The presentation emphasizes the need to assess and manage risks, respond to market dynamics, and evaluate non-financial factors for long- term success. Overall, Fruitylicious aims to capitalize on its projected ROI while remaining adaptable and focused on delivering high-quality, healthy desserts to customers.